SISTEM PERHITUNGAN HARGA POKOK PRODUKSI PADA PERUSAHAAN FARMASI PT. BALATIF DENGAN METODE PROCESS COSTING - Handojo, Andreas; Joesoef, Robby Adrian; ., Yulia (Institute of Research and Community Outreach - Petra Christian University, 2009)
Nowadays, PT. Balatif has the calculation system for production cost that can only include the calculation of cost of materials based on standard Bill of Material (BOM), while record of factory overhead cost, direct labor cost and report that relating to the calculation of Cost of Goods Manufactured of product still cannot be handled by the system. So that the current costs that really occurred in the production process will be difficult to trace and the production cost not based on reality process. Based on that problem, this research design a system to calculate production cost that can handle that problem. This application used Microsoft Visual Studio .Net 2005 as the programming tool and Oracle 10g as the database. Results that obtained from the application that have been made are raw material usage can be saved based on BOM or additional, machine usage, operator usage, and so on associated with the production process. In addition, the application that has been made can be used to allocate the costs that occur during the production process and to generate reports related to the calculation of Cost of Goods Manufactured of a product automatically.